Characterization of Mango-ginger (Curcuma amada Roxb.) Germplasms Through Isozyme Analysis - Moharana, RL; Chatterjee, R; Mondal, N; Basu, AK (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Mango-ginger, isozyme, characterization Bangladesh j. genet. biotechnol. 7(1&2): 5-9 2006 (June & December)